Vancomycin-Resistant Enterococci: Current Understandings of Resistance in Relation to Transmission and Preventive Strategies - Ivana Mareković; Manda Markanović; Joško Lešin; Mario Ćorić (Pathogens, 2024)
Due to the limited treatment options and increased mortality rates, infection prevention and control strategies have been implemented for many years to mitigate dissemination of vancomycin-resistant enterococci (VRE) within healthcare settings. The overview provides an insight into the most recent research, particularly the pathogen’s resilience in the healthcare environment, and the critical need for infection control strategies, which are currently being scrutinized by some researchers. The notable resilience of enterococci to various environmental conditions highlights the necessity for investigations into innovative technologies capable of effectively targeting the biofilm produced by enterococci on hospital surfaces. A critical approach to traditional infection control strategies is becoming more accepted worldwide, taking into account the epidemiological situation in the given healthcare setting as well as specific characteristics of a patient. For certain high-risk patient populations, traditional infection control strategies including CP and screening should not be omitted. Additionally, further investigation into the resistance mechanisms of available antimicrobial agents is essential, as is research into their potential association with specific successful clones through WGS genotyping, to pre-emptively mitigate their spread before it escalates.